CAPECO: Cost evaluation of community acquired pneumonia managed in primary care. Issue 19 (27th April 2016) - Personne, V.; Chevalier, J.; Buffel du Vaure, C.; Partouche, H.; Gilberg, S.; de Pouvourville, G.
Abstract: Background: Estimating the economic burden of community acquired pneumonia (CAP) managed in ambulatory setting is needed in France since no data are available. Method: A retrospective study (CAPECO) was conducted based on a prospective French study describing patients with suspected CAP managed in primary care (CAPA). The aim of the CAPECO study was to estimate and explain medical costs of a disease episode in CAP patients only followed in ambulatory care and in hospitalised patients. Primary endpoints were the direct medical costs, impact on productivity and costs of incident CAP over one year. Secondary endpoint was to describe predictive factors of costs, hospital admission and stay length. Results: In this cohort of 886 patients, resulting in an incidence of CAP of 400 per 100, 000 inhabitants per year, the mean direct medical cost of a disease episode of CAP was €118.8 for strictly ambulatory patients with an equal weight for medical time, drugs, diagnostic procedures and tests. This direct cost was €102.1 before admission for patients who were finally hospitalised. The mean cost of hospital admissions was €3522.9. Main predictive factors of hospital admission and stay length were respectively a history of chronic respiratory disease and older age. Factors of direct medical cost were prescribing X-ray examination and having a positive X-ray. The impact of a disease episode on productivity was €1980 (sd 1400) per ambulatory episode and €5425 (sd 4760) per episode leading to hospital admission. Conclusion: Costs per ambulatory episode were modest but increased substantially in hospitalised patients, who were more numerous when chronic respiratory disorders were present and in the elderly. Indirect costs were significant. Deciders should thus consider both direct and indirect costs when assessing preventive interventions in the context of this disease.